Analysis of material flow and resource utilization in production systems with the use of turntables - Poloczek Roksana (Production Engineering Archives)
The article explores the analysis of material flow and resource utilization in production systems using rotary tables. Through the use of simulation models in FlexSim software, the study evaluates different configurations of production lines and their impact on system performance. Three scenarios are examined, involving variations in the number of production lines and rotary tables, to identify the balance between system stability and flexibility. The findings emphasize the role of rotary tables in managing material flow effectively and ensuring smooth operations. The study also discusses the advantages of simulation in predicting operational outcomes and supporting decision-making processes, such as optimizing material flow paths and managing production resources. Challenges, including variability in system performance and the complexity of balancing multiple lines, are also addressed. The results demonstrate the value of simulation tools like FlexSim in understanding and improving production systems, highlighting their importance in strategic planning and enhancing the adaptability of modern manufacturing processes.